Initiative for Heavily Indebted Poor Countries : Issues Related to the Sunset Clause. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper responds to the Boards' request to present a proposal addressing country eligibility under the HIPC Initiative sunset clause and discuss related issues. It builds on an informal note to the Boards which explored a number of options to deal with the sunset clause of the HIPC Initiative, which is scheduled to take effect at end-2006. It addresses the concerns raised by Directors in their discussion of the note in July 2006 and proposes that the sunset clause be allowed to take effect and the countries that are assessed to have met the income and indebtedness criteria based on end-2004 data be grandfathered. In response to concerns raised by Directors, it also discusses the issue of a permanent exit from the Initiative for countries wishing to do so.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Arrears; Country; IMF Country Document; PP; Total HIPC Initiative; Afghanistan, Islamic Republic of